The Boston Cosmopolitans : International Travel and American Arts and Letters, 1865-1915 - Rennella, Mark (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This book traces the progression of cosmopolitanism from the private experience of a group of artists and intellectuals who lived and worked in Boston between 1865 and 1915 to finished works of monumental art that shaped public space.